Influence of the Electric Reactor Magnetic Field on the Electromagnetic Relays - Morozionkov, J.; Virbalis, J. A. (Elektronika ir Elektrotechnika, 2010)
The strongest magnetic fields are near the electric reactors in the electric plants. These fields can do the unwished action to electromagnetic relays. The outer magnetic field can delay the action of direct-current relay and awake the contact vibration. The alternating-current relays can not act, when the outer magnetic flux exceeds the flux created by the relay excitation coil some times. The especially dangerous is the leakage magnetic flux which acts in the air gap of relay but it passes by the excitation coil. The induction relay can not act, when the outer magnetic flux is equal to some tens percentages of magnetic flux which creates the excitation coil of the relay.